ANALISIS FUNDAMENTAL CRYPTOCURRENCY TERHADAP FLUKTUASI HARGA PADA MASA PANDEMI - Luxmana, David Bima; Oktafiyani, Melati (Faculty of Economic and Business Universitas STIKUBANK, 2022)
This research analyzes cryptocurrency fundamentals during the pandemic COVID-19 significantly affected cryptocurrencies during a brief period of financial panic. Technological advances resulted in the shift of traditional currencies towards digitalization. Volume and market cap variables are used as independent variables. The cryptocurrencies in this study are Bitcoin, Ethereum, Binance Coin, Ripple, and Dogecoin, which have the top 10 largest market capitalization. The research data was taken on the CoinMarketcap.com website from the beginning of the pandemic in Indonesia in March 2020 – to February 2021. The results showed that the Market Cap of Bitcoin, Ethereum, Binance Coin, Ripple, and Dogecoin had a significant effect on the price. Furthermore, the volume of Bitcoin, Ethereum, Binance, and Dogecoin has an effect and is significant on the price. In comparison, Ripple Volume has no effect and is not significant to the price. This implies that highly speculatively priced cryptocurrencies have the same fundamental value as stock prices.